Theory and Methodology for Financial Infrastructure of FDI in Developing Countries: the BRICS Case - Wang, Lei; Nagapetyan, Artur R.; Lutsenko, Elizaveta A.; Viktor N. Pakhmutov, Viktor N. (International Review of Management and Marketing, 2016)
Global investment imbalance is suggested to be one of three main global economic problems. The purpose of this paper is to analyse possible solutions of global investment imbalance with methods of behavioral economy. The existing models of financial valuation tools that proved to be effective in the developed economies cannot be used effectively for the developing ones. The emphasis of the study is on BRICS countries as a special agent of emerging economies' interests. By means of an analytical model and panel data, the paper is to modify financial assessment tools with a regard for developing countries' specific features. The main contribution of this paper is to deepen the concept of pricing deformation, which is characterized in that the behavioral abnormalities are considered as the basis of deformations. The results are to reveal how to employ risk return trade-off concept on investing in rapidly developing countries. Keywords: BRICS, foreign direct investment, financial assessment tools JEL Classifications: N2; O16